2012
DOI: 10.1186/1471-2334-12-54
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pulmonary TB and spoligotype pattern of Mycobacterium tuberculosis among TB suspects in a rural community in Southwest Ethiopia

Abstract: Background In Ethiopia where there is no strong surveillance system and state of the art diagnostic facilities are limited, the real burden of tuberculosis (TB) is not well known. We conducted a community based survey to estimate the prevalence of pulmonary TB and spoligotype pattern of the Mycobacterium tuberculosis isolates in Southwest Ethiopia. Methods A total of 30040 adults in 10882 households were screened for pulmonary TB in Gilgel Gib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 14 publications
1
36
4
Order By: Relevance
“…The 130.2/100,000 adjusted prevalence estimate of BCTB cases identified in this study is higher than the 34/100,000 reported from China and the 76/100,000 from Southwest Ethiopia [12]. Nonetheless, it is lower than the 169/100,000 report from Northern Ethiopia [27] and the 278/100,000 from the Lao PDR [28].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The 130.2/100,000 adjusted prevalence estimate of BCTB cases identified in this study is higher than the 34/100,000 reported from China and the 76/100,000 from Southwest Ethiopia [12]. Nonetheless, it is lower than the 169/100,000 report from Northern Ethiopia [27] and the 278/100,000 from the Lao PDR [28].…”
Section: Discussioncontrasting
confidence: 64%
“…Conversely, it is higher than previous reports that ranged from 30 to 80/100,000 population in different parts of the country [12, 14, 30], the 90/100,000 from Eritrea [31] and the 95/100,000 from Bangladesh [32]. Still, it is lower than the145/100,000 population reported from Vietnam [33], and the 169/100,000 population reported from Northern Ethiopia [27] and India [34].…”
Section: Discussioncontrasting
confidence: 64%
“…A tuberculosis survey conducted from October 2010-June 2011 in Ethiopia, indicated 0.2% (110/51667) culture positivity from pulmonary TB suspected cases [48]. A study conducted in the rural community of South-west Ethiopia revealed a culture positivity of ~4% (17/482) [49]. The current result lies within the limits of the two findings.…”
Section: Discussionsupporting
confidence: 71%
“…The prevalence of bacteriologically positive TB was reported by sex in 56 surveys with 2.2 million participants in 24 countries [29,30,32,33,35,36,3844,47–51,53,55,56,5860,65–67,69–74,82,84,85,87,89–94,97,101,102,104,105,107,110112]. Forty surveys with 1.7 million participants in 22 countries reported the prevalence of smear-positive TB by sex [35,40,43,44,48–51,53,55,56,5860,65–67,69–71,73,74,85,87,89,90,92,94,97,101,102,105,107,110,111].…”
Section: Resultsmentioning
confidence: 99%